Can smallholder farmers buffer rainfall variability through conservation agriculture? On-farm practices and maize yields in Kenya and Malawi - Boillat, Sébastien; Jew, Eleanor KK; Steward, Peter R.; Speranza, Chinwe Ifejika; Whitfield, Stephen; Mkwambisi, David; Kiteme, Boniface; Wambugu, Grace; Burdekin, Oliver J; Dougill, Andrew J. (IOP Publishing, 2019)
Reduced tillage, permanent ground cover and crop diversification are the three core pillars of Conservation Agriculture (CA).We assess and compare on-farm effects of different practices related to the three pillars ofCA on maize yields under ENSO-driven rainfall variability in Kenya and Malawi. Reduced tillage practices increased yields per hectare by 250 kg on average in Malawi under belowaverage rainfall conditions and by 700 kg in Kenya under above-average rainfall, but did not have any significant effect on yields under below-average rainfall conditions in Kenya. Ground cover had a positive impact on yields in Malawi (dry conditions) but not in Kenya (both dry and wet conditions), where mixed crop and livestock systems limited this practice. Crop diversification had positive impacts in Kenya (both dry and wet conditions), where maize-legume crop rotation is practiced, but not in Malawi where landholdings are too small to allow rotation. Our findings suggest that isolated CAtechniques can have positive effects on yields even after only a few years of practice under variable rainfall conditions. This strengthens empirical evidence supporting the value ofCA in resilience building of agricultural systems, and suggests that both full and partial adoption ofCApractices should be supported in areas where climate change is leading to more variable rainfall conditions.